Toba Batak Progressivism and Language Maintenance - Cartalyna Napitupulu (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1998)
Tabs Batak people originate from Tapanuli, North Sumatra around Lake Toba. This tribe has their own language which is TB language. Compared with other tribes, TB people started their contact with other cultures later. The eastern part of Indonesia, fOr example, had been having contact with the Portuguese since the sixteenth century while the TB people only started in 1861. Later, the TB also had contact with the Dutch, the British and the Germans which resulted in the spread of Christianity amongst TB people. It was the missionaries or the Batak mission who first encouraged education amongst the TB because they wanted to encourage the TB to understand the Gospel. Thus, the formal education in the T8 areas started after the arrival of Christianity. Meanwhile, education brought by the Christian mission gave rise to the TB ambition towards progress or what they called Hamajuon Salak or 'Batak Progressivism'. These missionarires not only gave education in the TB areas but also sent the TB members overseas. Some researchers like Kruger and Peeeesen believe that TB people were cannibals in the past, even after the penetration of Christianity began. They suspected that missionaries like Lyman and Munson were eaten bv the TB (Pedersen, 1970).